Campuran Tulang Sapi Dengan Asam Organik Untuk Meningkatkan PTersedia dan Pertumbuhan Tanaman Jagung di Inceptisol - Andi Pratama; Mukhlis Mukhlis; T. Sabrina (Universitas Sumatera Utara, 2014)
The research aimed to determine the effect of a mixture of cow bone ash with organic acids on Pavailable inceptisol soil and growth of maize (Zea mays L.). The research was conducted in thegreenhouse and analyzed in the laboratory of research and technology of Agriculture Faculty ofNorth Sumatera University of Medan from May-October 2013. The research design was nonfactorialrandomized block design consisting of 13 treatments with 3 replications that is: Control,T1K (cow bone ash 166.7 g), T1S1 (cow bone ash 166.7 g + citric acid 2% 500.1 mL), T1A1 (cowbone ash 166.7 g + acetic acid 2% 500.1 mL), T1L1 (cow bone ash 166.7 g + lactic acid 2%500.1mL), T2K (cow bone ash 333.4 g), T2S2 (cow bone ash 333.4 g + citric acid 2% 1000.2 mL),T2A2 (cow bone ash 333.4 g + acetic acid 2% 1000.2 mL), T2L2 (cow bone ash 333.4 g + lactic acid2% 1000.2 mL), T3K (cow bone ash 500.1 g), T3S3 (cow bone ash 500.1 g + citric acid 2% 1500.3mL), T3A3 (cow bone ash 500.1 g + acetic acid 2% 1500.3 mL), dan T3L3 (cow bone ash 500.1 g +lactic acid 2% 1500.3 mL).The result of research indicated that application of 500.1 g cow bone ash+ citric 1000.2 mL citric acid 2% was the highest increasing soil pH (6.78), P available (20 ppm),P-uptake of plants (0.26 g P/plant), plant shoot dry weight (51.66 g), plant root dry weight (14.23),and plant height (187.27 cm) compared with other treatments.Keywords: Cow Bone, Organic Acid, Phosphate, Inceptisol